2017
DOI: 10.1080/19390211.2017.1334735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Goat's Milk Supplementation with Tamr on Free Fatty Acids, Antioxidant Activity, and Probiotic Bacteria of Bio-Rayeb Milk

Abstract: Tamr (dried dates) has a high sugar content, essential vitamins, and high nutrient density. Dairy products still are the most typical carriers of probiotic bacteria. Six treatments of bio-rayeb milk were manufactured from goat's milk fortified with 5%, 10%, 15%, 20%, and 25% Tamr using ABT-5 culture. Rayeb milk containing tamr had lower pH and fat and higher carbohydrate, total solids, dietary fiber, ash, total protein, water-soluble nitrogen, and total volatile fatty acids. Mixing tamr with bio-rayeb milk inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, only a few studies to date have evaluated the improvement of the flavor of goat milk products with probiotics (Costa et al. ; Hamad, Ismail, & Elraghy, ; Silva et al., ).…”
Section: Potential Beneficial and Nutritional Features Of Goat Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies to date have evaluated the improvement of the flavor of goat milk products with probiotics (Costa et al. ; Hamad, Ismail, & Elraghy, ; Silva et al., ).…”
Section: Potential Beneficial and Nutritional Features Of Goat Milkmentioning
confidence: 99%
“…The flavor characteristics of certain goat milk products remain problematic, but the addition of probiotic cultures could contribute to improving their sensory properties. However, only a few studies to date have evaluated the improvement of the flavor of goat milk products with probiotics (Costa et al 2014;Hamad, Ismail, & Elraghy, 2018;Silva et al, 2017).…”
Section: Goat Milk As a Probiotic Carrier Foodmentioning
confidence: 99%
“…They have shown numerous health benefits, including improving gut health, reducing inflammation, and boosting the immune system 13 . Also, Hamad et al 14 revealed that adding probiotics and tamr to goat bio rayeb milk can improve its nutritional value and, sensory quality, overall acceptability, also significantly increase the acidity, protein content, and probiotic bacteria counts of bio rayeb, making it a more convenient and accessible probiotic product for consumers. Combining essential oils and traditional dairy products, such as rayeb milk, presents a promising approach to improving dairy products' nutritional and health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Newly, standardized and sterilized Rayeb milk is made in dairy products plants using whole milk and ABT culture. In the same context, Hamad et al [8] manufactured bio-Rayeb milk from goat's milk supplemented with Tamr (dried dates). They cleared that mixing Tamr with bio-Rayeb milk increased nutritional value by decreasing saturated fatty acids and increasing α-linolenic, linoleic, oleic acids, and antioxidant activity levels.…”
Section: Introductionmentioning
confidence: 99%